Sources of real exchange rate fluctuations in new EU member countries - Rajmund Mirdala (FIW - Research Centre International Economics, 2015)
Fixed versus flexible exchange rate dilemma has become a subject of rigorous academic discussions for decades. Advantages of exchange rates flexibility contrasted benefits of exchange rate stability though a phenomenon known as the fear of floating favoured exchange rate variability and its positive effects on economies. Relative diversity in the exchange rate regimes in EU11 countries motivated many authors to investigate the sources of their real exchange rate volatility provided that even fixed exchange rates may fluctuate via adjustments in prices and wages. However, fixed exchange rate perspective associated with Eurozone membership may induce changed patterns in the real exchange rate determination in countries that benefit from nominal exchange rate flexibility prior to euro adoption. In the paper we analyse sources of real exchange rates fluctuations in EU11 countries. SVAR methodology and impulse-response functions will be employed to examine the responsiveness of real exchange rates to the underlying structural shocks by employing SVAR methodology. Our results indicate an increased responsiveness of real exchange rates in EMU non-member countries to demand and supply shocks, particularly due to the effects of the crisis period. At the same time, real exchange rates in EMU member countries became more responsive to nominal shocks.
Keywords: C32; E52; 330; real exhange rates; exogenous shocks; economic crisis; structural vector auto regression; impulse-response function